ANALYSIS MATHEMATICS TEACHER EXPERIENCE IN DEVELOPMENT OF LEARNING MEDIA BASED ON CANVA AND OPEN BROADCASTER SOFTWARE (OBS) IN THE MERDEKA CURRICULUM - Wahyu Henky Irawan; Queen Firdausi; Neni Ratnasari; Umi Lailatus Sa'adah (MATEMATIKA DAN PEMBELAJARAN, 2025)
This research is motivated by the need for innovation in learning media that supports the implementation of the Merdeka Curriculum, but the adoption of technology by teachers in the field is still minimal. This study aims to analyze the responses and experiences of mathematics teachers in developing learning media based on Canva and Open Broadcaster Software (OBS) in the Merdeka Curriculum. The research method uses a qualitative phenomenological approach with data collection techniques through interviews and online questionnaires to mathematics teachers who have used Canva and OBS. The results of the study show that Canva is widely used to create interesting visual materials, while OBS is used to record or broadcast learning videos. The main obstacles faced by teachers are limited time, access to premium features, and lack of technical training. These findings indicate the need for intensive training, technical support, and provision of access to digital resources to support the integration of technology-based learning media in the Merdeka Curriculum.